(untitled) (Research, Society and Development, 2022)
Dental Enamel is the most mineralized body tissue and and changes during its formation will lead to permanent damage, because it does not remodel throughout the years. Enamel lesions can affect both dentitions and many times it can cause discomfort to patients, such as Enamel Hypoplasia, Amelogenesis Imperfecta, Dental Fluorosis and Dental Caries. These abnormalities are characterized by white stains and opacities which can have very similar clinical characteristics, making clinical diagnosis and treatment difficult. Therefore, the aim of this study was to identify the level of knowledge of the students from the Dentistry course of the Universidade Federal de Campina Grande, Patos campus, regarding diagnosis and treatment of lesions in dental enamel. This is a cross-sectional study, observational, inductive, comparative, descriptive and taking as strategy data collection and specific questionnaire. From the questionnaire applied, it was observed that the marority of the graduate students had difficulties at diagnosing and proposing an adequate treatment plan for enamel abnormalities, hypoplasia and fluorosis being very mild lesions that highlight in this measure. However, caries lesions and amelogenesis imperfecta were the ones that had greater percentage of right answers with 70,0% and 70,7%, respectively. Furthermore, the highest percentage of correct answers for diagnosis was by the 10th period undergraduates, while the 9th period had the highest percentage of correct answers for treatment. In sum, students evaluated themselves with difficulty at diagnosis and treatment plan of the lesions and pointed out to have little knowledge regarding this subject.